Comparative Genomics of Color Morphs In the Coral Montastraea cavernosa. Issue 1 (December 2017) - Jarett, Jessica; MacManes, Matthew; Morrow, Kathleen; Pankey, M.; Lesser, Michael
Abstract Montastraea cavernosa is a common coral in the Caribbean basin found in several color morphs. To investigate the causes for brown and orange morphs we undertook a genomics approach on corals collected at the same time and depth in the Bahamas. The coral holobiont includes the host, symbiotic dinoflagellates (Symbiodinium spp.), and a diverse microbiome. While the coral host showed significant genetic differentiation between color morphs both the composition of theSymbiodinium spp. communities and the prokaryotic communities did not. Both targeted and global gene expression differences in the transcriptome of the host show no difference in fluorescent proteins while the metatranscriptome of the microbiome shows that pigments such as phycoerythrin and orange carotenoid protein of cyanobacterial origin are significantly greater in orange morphs, which is also consistent with the significantly greater number of cyanobacteria quantified by 16S rRNA reads and flow cytometry. The microbiome of orange color morphs expressed significantly more nitrogenase (nif H) transcripts consistent with their known ability to fix nitrogen. Both coral andSymbiodinium spp. transcriptomes from orange morphs had significantly increased expression of genes related to immune response and apoptosis, which may potentially be involved in maintaining and regulating the unique symbiont population in orange morphs.